GESTÃO DE PESSOAS E DE INSTITUIÇÕES DE ENSINO: UM EXERCÍCIO DE SOMA POSITIVA - Marlon Jackson Tafner (Universidade Federal de Santa Catarina, 2011)
For many people, winning means other`s loss. It means that two or more parts compete in a fixed base where the winner gets the best part of it. This kind of relation is characterized for being hard, based on the price and not on the value. They are, thereby, adverse relations and do not promote the development of the parts. This article explores the many was of the relation among organizations approaching and, inevitable, among people, trying to embrace a different approach from the one used by the researches, university students and practitioners when they pore on the win-win relations among organizations. The considerations of the human-science-aspects results, combined with the best that the traditional approaches have to offer, may reveal themselves very important and renewable in the institute and the maintenance of the win-win relations.